A preliminary study on the cryopreservation of the Philippine tiger shrimp, Penaeus monodon (Fabricius) embryos. - Pet, Eugene Stan Engelbert A
Tiger shrimp embryos at gastrula (3.5 hours old) and early embryonic nauplii stage (11 hours old) were tested for cryoprotection toxicity using methanol (MET), Dimenthyl Sulphoxide (DMSO) and 1-2 Propane di-ol (PROH) at 4, 8 and 12 concentrations. Survival and hatching as well as the effects of freezing were observed. Highest survival was observed at gastrula stage treated with methanolat 4 concentrations. Early embryonic nauplii stage exhibited low resistance towards the three cryoprotectants. The integrity of the hatching envelopes was used as the basis for evaluating the effects of freezing in the embryos. Embryos were frozen using alcohol bath preconditioned for 1 hour at - 16 degrees centigrade. All frozen embryos treated with methanol and DMSO at 4 and 8 concentrations died and exhibited disruption of cytoplasm and rupture of hatching envelope.